1985
DOI: 10.1007/bf00276226
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements and the enhancement of edges

Abstract: A mathematical examination of retinal photochemistry leads to a hypothesis for Mach band phenomena based on eye movements. This retinal model suggests why minimally distinct borders fade under eye fixation and agrees qualitatively with subjective measures of border contrast as a function of overall field luminance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A visual illustration of the lateral inhibition mechanism is provided in figure 1. Alternative explana tions for Mach bands exist: Woods et al [ 18] suggested that the visual Mach band phenomenon is due to eye movement and photochemical properties of the retina via transiently stimulated photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…A visual illustration of the lateral inhibition mechanism is provided in figure 1. Alternative explana tions for Mach bands exist: Woods et al [ 18] suggested that the visual Mach band phenomenon is due to eye movement and photochemical properties of the retina via transiently stimulated photoreceptors.…”
Section: Discussionmentioning
confidence: 99%